2013
DOI: 10.1167/iovs.13-12350
|View full text |Cite
|
Sign up to set email alerts
|

Macular Choroidal Thickness and Volume in Healthy Pediatric Individuals Measured by Swept-Source Optical Coherence Tomography

Abstract: The macular choroidal thickness and volume in the pediatric individuals were significantly larger than those in the adults. The pediatric choroidal thinning with increasing age is more rapid in the central area. Pediatric choroidal thickness is associated with several systemic or ocular parameters, especially the axial length and body mass index. These differences should be remembered when the choroidal thickness is evaluated in pediatric patients with retinochoroidal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
84
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 32 publications
17
84
1
Order By: Relevance
“…8,12,14 The choroid in the macular region was thickest in the temporal sector and thinnest in the nasal sector, which was similar to that in previous studies carried out in pediatric populations. 7,8,[10][11][12][13]15 The mean global PPCT in our study (136 6 33 lm) was also smaller than the mean PPCTs reported by a previous study (165 6 34 lm). 22 Age, race, refractive status as well as the instruments and protocols used may contribute to these differences.…”
Section: Varied Cht At the Posterior Polesupporting
confidence: 88%
See 1 more Smart Citation
“…8,12,14 The choroid in the macular region was thickest in the temporal sector and thinnest in the nasal sector, which was similar to that in previous studies carried out in pediatric populations. 7,8,[10][11][12][13]15 The mean global PPCT in our study (136 6 33 lm) was also smaller than the mean PPCTs reported by a previous study (165 6 34 lm). 22 Age, race, refractive status as well as the instruments and protocols used may contribute to these differences.…”
Section: Varied Cht At the Posterior Polesupporting
confidence: 88%
“…In previous studies, there was a decreasing ChT with increasing age in Asian children and an increasing ChT with increasing age in white children in the central foveal region. [6][7][8][10][11][12][13][14][15] Moreover, one research with large sample size carried our by our study group showed that age was positively related to ChT in emmetropic and mild myopic (SE > À2.00 D) children, while no relationship was found between age and ChT in children with SE À2.00 D. 16 Another our previous study also showed that the ChT was associated with height, 11 while height was not included in the model in this study. Different age distribution of the samples and different measurement methods of ChT may have contributed to these markedly different results.…”
Section: Independent Factors Of Cht Throughout the Posterior Polementioning
confidence: 44%
“…Similar studies carried out on children have also revealed an inverse correlation between ChT and axial length (15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Original Research Articlesupporting
confidence: 68%
“…Recently, there have been several attempts to use swept-source OCT (SS-OCT) to evaluate CT and CV [11,16,17]. The SS-OCT system uses a light source with a long wavelength-sweeping laser centered at 1,050 nm, yielding an 8-μm axial resolution in tissue and with an imaging speed of 100,000 A-scans/s, which is more rapid than the spectral-domain OCT (SD-OCT) A-scan rate [17,18].…”
Section: Introductionmentioning
confidence: 99%